Christianity and the notion of nothingness : contributions to Buddhist-Christian dialogue from the Kyoto school - Mutō, Kazuo, 1913-1995. (Philosophy of Religion - World Religions, 2012)
This publication by Muto Kazuo is a significant Christian contribution to the predominantly Buddhist "Kyoto School of Philosophy." Muto proposes a philosophy of religion in order to overcome the claim for Christian exclusivity, as proposed by Karl Barth and others. On such a foundation, he investigates the possibilities for mutual understanding between Buddhism and Christianity. Thereby he engages in a critical exchange with the Kyoto School philosophers Nishida, Tanabe, and Nishitani. Throughout his discourse, Muto applies their method of logical argument (the "dialectic" of soku ) to the dialogue between Christianity and Buddhism. He thus opens up new perceptions of Christian faith in the Asian context and, together with his Buddhist teachers, challenges the modern Western dialectical method of reasoning.